25th Annual European Real Estate Society Conference 2018
DOI: 10.15396/eres2018_156
|View full text |Cite
|
Sign up to set email alerts
|

The 2015 European Refugee Crisis and Residential Housing Rents in Germany

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…In further analyses, we exploit for identification exclusively variation in exposure to RRCs that is arguably exogenous to (prospective) local residents' preferences by considering only property located in counties adjacent to counties that housed RRCs, which eliminates the possibility that local lobbyists' in treatment, respectively control regions, exerted an influence on the decision of county-level officiating bodies where exactly to place new RRCs within administrative county regions. These explorations corroborate our finding of a negative effect on house price growth in vicinity of RRCs, which adds to and complements related findings on refugee centers in the Netherlands (Daams et al, 2019;Dröes and Koster, 2019), refugee shelter opening announcements in the city of Gothenburg in Sweden in the wake of the 2015 European Refugee Crisis (van Vuuren et al, 2019), and associated findings of a negative impact of the scale of refugee immigration in late 2015 on rental price growth for residential housing (at county level) in Germany (Kürschner Rauck and Kvasnicka, 2018). These findings may all be a reflection of NIMBYism related to regional differences in natives' perceptions of potential adverse externalities associated with large scale refugee settlements, particularly if they are concentrated, and they bear implications for the design of public policies in handling future receptions of refugees, i.e.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…In further analyses, we exploit for identification exclusively variation in exposure to RRCs that is arguably exogenous to (prospective) local residents' preferences by considering only property located in counties adjacent to counties that housed RRCs, which eliminates the possibility that local lobbyists' in treatment, respectively control regions, exerted an influence on the decision of county-level officiating bodies where exactly to place new RRCs within administrative county regions. These explorations corroborate our finding of a negative effect on house price growth in vicinity of RRCs, which adds to and complements related findings on refugee centers in the Netherlands (Daams et al, 2019;Dröes and Koster, 2019), refugee shelter opening announcements in the city of Gothenburg in Sweden in the wake of the 2015 European Refugee Crisis (van Vuuren et al, 2019), and associated findings of a negative impact of the scale of refugee immigration in late 2015 on rental price growth for residential housing (at county level) in Germany (Kürschner Rauck and Kvasnicka, 2018). These findings may all be a reflection of NIMBYism related to regional differences in natives' perceptions of potential adverse externalities associated with large scale refugee settlements, particularly if they are concentrated, and they bear implications for the design of public policies in handling future receptions of refugees, i.e.…”
Section: Introductionsupporting
confidence: 89%
“…Research on the recent mass inflow of Syrian refugees to Turkey also found positive price effects, particularly for rental property in the upper price segment and property located in native-dominated residential areas, which may be attributable to an increase in natives' demand for residential segregation with respect to ethnicity (Tumen, 2016;Balkan et al, 2018). Studies that have found negative price effects of forced migration for residential property explored the link between (general) refugee migration over the years 2004 to 2015 and UK house prices (Lastrapes and Lebesmuehlbacher, 2018), price penalties suffered by Dutch property in vicinity to asylum seeker reception centers over the years 2009 to 2017 (Daams et al, 2019) as well as 1990 to 2015 (Dröes and Koster, 2019), and refugee migration fuelled by the Syrian refugee crisis and perceived housing quality and predicted rents in Jordan (Alhawarin et al, 2018) or apartment prices (van Vuuren et al, 2019) and housing rents (Kürschner Rauck and Kvasnicka, 2018) in major European refugee recipient countries.…”
Section: Previous Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Our identification strategy relies on the substantial idiosyncratic variation in the assignment of asylum seekers to German counties that is accompanied by a so-called 'domicile obligation', which requires asylum welfare benefit recipients to stay in their assigned county. The same dispersal policy has also been exploited for investigating the effects of the spatial allocation of asylum seekers on regional outcomes in Germany [14][15][16]. In order to capture variation in local labor market conditions as well as national policy dynamics, we additionally rely on an extensive set of fixed effects, focusing on within-variation.…”
Section: Introductionmentioning
confidence: 99%